Geoquímica de Elementos Terras Raras (ETRs) como indicadores da proveniência dos sedimentos de albufeiras dominicanas - Fonseca, Rita; Araújo, Joana; Pinho, Catarina; Nogueira, Pedro; Araújo, Alexandre (Universidade de Évora, 2019)
The geochemical composition of rare earth elements (REE) in the bottom sediments from two Dominican reservoirs, in soils and rocks from respective drainage basins, was studied in order to identify the possible sources of the deposited materials. The REE contents of the 3 components were normalized to NASC, and the light/heavy REE ratio, the Ce and Eu anomalies and a few fractionation parameters were determined. The data point to a clear depletion of REE from the sources, an enrichment in light REE and in some middle elements (Eu, Er), positive anomalies of Eu and mostly positive of Ce, which represents the element with greater spatial and temporal variation, related to chemical variation of the environment. The REE distribution patterns are notoriously more homogeneous in sediments, revealing a uniform sedimentation over the reservoirs and between distinct seasonal periods, not allowing the definition of sources for each reservoir sector. Bivariate diagrams between the fractioning parameters of light-middle-heavy REE, where the data of sediments, soils and rocks were plotted, allowed a good discrimination of the main sources of the materials deposited in these reservoirs.
Geochemistry of Rare Earth Elements (REE) as a fingerprint of sediment provenance in Dominican Dam Reservoirs
Keywords: Geochemical analysis; Rare earth elements; Sediments provenance; Dominican dam reservoirs